Macroeconomic management amid ethnic diversity: Fifty years of Malaysian experience - Jayant Menon (Asian Development Bank Institute (ADBI), 2008)
This paper examines the role that macroeconomic policy management has played in the Malaysian development experience. Given the multiracial nature of Malaysian society, macroeconomic policy has not only been about economic stabilization, but also about addressing income disparities along racial lines in order to preserve social harmony. The affirmative action program under the New Economic Policy was an important signaling device, and served to demonstrate that all should share in future growth. Its actual contribution is difficult to determine, because rapid economic growth and structural change were taking place concurrently. Although its resource cost was not a major drag on growth in the past, the slowdown in FDI inflows and exports post-crisis, combined with demographic change, implies that reforms may be necessary to ensure sustainability, going forward. The key lesson to come from the Malaysian experience is that in a small open economy, the task of achieving the conflicting objectives of growth and equity is facilitated by a long-term commitment to an open and liberal trade and investment policy regime.
Keywords: E60; E63; E65; F41; 330; Wirtschaftspolitik; Entwicklung; Malaysia